1993
DOI: 10.1016/0014-5793(93)80372-2
|View full text |Cite
|
Sign up to set email alerts
|

A Glu329→ Gln variant of the α‐subunit of the rat kidney Na+K+‐ATPase can sustain active transport of Na+ and K+ and Na+K+‐activated ATP hydrolysis with normal turnover number

Abstract: An allelic variant of the ouabain-in~nsitive rat kidney Na',K+-ATPase a,-isoform was identified by chance in a cDNA library. The variant differed from the wild-type rat kidney Na',K'-ATPase by a single G-to-C base substitution in the cDNA, which on amino acid level gave rise to a glutamine in place of the glutamate residue G~u'*~ previously suggested as a likely donator of oxygen ligands for Na+ and K' binding. The variant cDNA was transfected into COS-1 cells and the transfectants expanded with success into s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The Kd values for both E327Q and D925L were higher, namely 7-7 and 6-4 mm, respectively. The 6-4-fold decrease in affinity observed for E327Q is similar to that observed in biochemical studies previously reported (Vilsen, 1993). The Kd values calculated from ATPase assays were 1P0, 3*7 and 1-9 for the rat a2*, E327Q and D925L proteins, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…The Kd values for both E327Q and D925L were higher, namely 7-7 and 6-4 mm, respectively. The 6-4-fold decrease in affinity observed for E327Q is similar to that observed in biochemical studies previously reported (Vilsen, 1993). The Kd values calculated from ATPase assays were 1P0, 3*7 and 1-9 for the rat a2*, E327Q and D925L proteins, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…The experiments of Koster et al (32), which show that the properties of the E786K mutant in Na,K-ATPase are rather similar to that of the wild type, do not fit in the model for Na,K-ATPase (27). In the latter model Glu 334 does not play a direct role, but mutagenesis experiments with Na,K-ATPase suggest that this residue is directly involved in K ϩ -binding (30,(33)(34)(35).…”
mentioning
confidence: 90%
“…The COOH-terminal amino acids, PEGLLA, are involved in ion binding. Mutations at the proline, glutamate, or the second leucine residue have been shown to alter the affinities for K ϩ and Na ϩ (30). In an analogous region of the sarcoplasmic reticular Ca 2ϩ pump, the residues EGL have been shown to be involved in Ca 2ϩ binding and transport and in the conformational changes associated with Ca 2ϩ transport (31).…”
Section: Na ϩ -Ca 2ϩ Exchanger Transmembrane Mutationsmentioning
confidence: 99%
“…Glu-199 is conserved among the three NCX-type exchangers, and the analagous glutamate in the Na ϩ , K ϩ , and Ca 2ϩ pumps is involved in ion binding and translocation (30,31). Conservative mutations at Glu-199 to either glutamine or aspartate resulted in non-functional exchangers.…”
Section: Na ϩ -Ca 2ϩ Exchanger Transmembrane Mutationsmentioning
confidence: 99%